Front Pages IJReSES Vol. 13, No. 2(2016) - Editorial Journal (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2016)
Front Pages IJReSES Vol. 13, No. 2(2016)  *Note: This cover is a revision of the Peer Reviewers section of the cover that was uploaded on May 26, 2017